2009
DOI: 10.1149/1.3216456
|View full text |Cite
|
Sign up to set email alerts
|

Partially Oxidized Niobium Carbonitride as Non-Platinum Cathode for PEFC

Abstract: Partially oxidized niobium carbonitride has been examined to apply to a non-platinum cathode for polymer electrolyte fuel cells ͑PEFCs͒. NbC 0.5 N 0.5 powder was partially oxidized in an inert gas containing 30 or 100 ppm O 2 at 1000°C for 10 h. NbO 2 or Nb 2 O 5 was observed in the X-ray diffraction patterns of the specimens. The catalytic activity for the oxygen reduction reaction ͑ORR͒ of the specimen that contained Nb 2 O 5 was higher than that of the specimens with NbO 2 and as-prepared NbC 0.5 N 0.5 . X-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…Several important studies on niobium carbonitride with partial oxidation, associated with Nb 2 O 5 species on the surface, have suggested that the surface oxide is the origin of catalysis 27,28 . However, the atomic-scale characterization indicates that there is no surface oxide on the samples and, thus, the origin of catalysis in our materials is the niobium-carbon complexes rather than the oxide.…”
Section: Resultsmentioning
confidence: 99%
“…Several important studies on niobium carbonitride with partial oxidation, associated with Nb 2 O 5 species on the surface, have suggested that the surface oxide is the origin of catalysis 27,28 . However, the atomic-scale characterization indicates that there is no surface oxide on the samples and, thus, the origin of catalysis in our materials is the niobium-carbon complexes rather than the oxide.…”
Section: Resultsmentioning
confidence: 99%
“…We used group 4 and 5 carbonitrides as starting materials for a partial oxidation [94][95][96][97][98]. We have mainly investigated partially oxidized tantalum carbonitride [94,97,98].…”
Section: Partial Oxidation Of Carbonitridesmentioning
confidence: 99%
“…We have developed the oxide-based non-Pt cathode catalysts [22,[48][49][50]65,66,72,[76][77][86][87][88][94][95][96][97][98]103]. Fig.…”
Section: Partial Oxidation Of Carbonitridesmentioning
confidence: 99%
“…They have high chemical stability in acidic media [21,22]. In addition, it has been reported that these compounds have some electrocatalytic activity for the ORR [23,24]. Transition metal oxides, such as zirconium oxide [25][26][27], titanium oxide [28][29][30], manganese oxide [31], tungsten oxide [32,33], niobium oxide [28,34,35], cobalt, and tin oxide [35] have been evaluated as electrocatalyst or catalyst-support for the ORR.…”
Section: Introductionmentioning
confidence: 99%